2020
DOI: 10.1002/er.5130
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of a novel fossil‐fuel–free energy storage system with a trans‐critical carbon dioxide cycle and heat pump

Abstract: This paper presents and analyzes a novel fossil-fuel-free trans-critical energy storage system that uses CO2 as the working fluid in a closed loop shuttled between two saline aquifers or caverns at different depths, one a low-pressure reservoir, and the other a high-pressure reservoir. Thermal energy storage and a heat pump are adopted to eliminate the need for external natural gas for heating the CO2 entering the energy recovery turbines. We carefully analyze the energy storage and recovery processes to revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…To show less reliance on fossil fuel, Hao et al presented a thermodynamic analysis of a fossil fuel free energy storage system with an investigation on the operational behavior of its key parameters. 35 By surveying the literature and considering the WHRS in a cement plant, it was clear that predicting the electrical power produced by the turbine using neural network was never undertaken. Accordingly, the main objective of this study was to apply ANNs to predict the generated power as well as investigate the actual performance of a WHRS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To show less reliance on fossil fuel, Hao et al presented a thermodynamic analysis of a fossil fuel free energy storage system with an investigation on the operational behavior of its key parameters. 35 By surveying the literature and considering the WHRS in a cement plant, it was clear that predicting the electrical power produced by the turbine using neural network was never undertaken. Accordingly, the main objective of this study was to apply ANNs to predict the generated power as well as investigate the actual performance of a WHRS.…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of solar energy reduced the consumption of fossil fuel in the plant, whereas the efficiency of the system was not altered much. To show less reliance on fossil fuel, Hao et al presented a thermodynamic analysis of a fossil fuel free energy storage system with an investigation on the operational behavior of its key parameters 35 …”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that the energy efficiency of these systems was between 52% and 59.6% 25 . Hao et al 26 proposed a novel energy storage system similar to a conventional CAES system that utilizes carbon dioxide as its working fluid, and also, used a heat pump to eliminate the use of natural gas in the discharging mode. Energetic and exergetic efficiencies of the system were obtained as 58.4% and 67.9%, respectively 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Hao et al 26 proposed a novel energy storage system similar to a conventional CAES system that utilizes carbon dioxide as its working fluid, and also, used a heat pump to eliminate the use of natural gas in the discharging mode. Energetic and exergetic efficiencies of the system were obtained as 58.4% and 67.9%, respectively 26 . An integrated wind/solar‐based CAES system was investigated by Ji et al 27 The round‐trip and exergy efficiencies of the proposed system were 61.2% and 65.4%, respectively 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 24 proposed a two‐reservoir CCES system, and they used a steady‐state mathematical model to evaluate the performance of the idealized two‐reservoir CCES system with a high‐temperature heat source (>800 K). Hao et al 25 proposed a novel transcritical CO 2 energy storage system with two saline aquifers or caverns at different depths and studied the operating characteristics under different depth conditions.…”
Section: Introductionmentioning
confidence: 99%